2016
DOI: 10.21037/jgo.2015.10.08
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of rectal cancer after radiotherapy with a long or short waiting period before surgery, a descriptive clinical study

Abstract: Background: Radiotherapy and surgery have shown to improve local control and survival in rectal cancer.There are two applied schedules; radiotherapy with a long or short waiting period before surgery. The effect on survival and recurrence of both schedules was studied.Methods: All consecutive patients with rectal cancer in the period 2002-2008 were included. Data were gathered on survival, tumour stage, co-morbidity score, and cause of death. The patients were divided in three groups: group 1 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Whether a long or short waiting period after radiotherapy is necessary still is a matter of debate (11,12). In the cohort diagnosed and treated in the Zaans Medisch Centrum, a longer waiting period results in a better outcome (13).…”
Section: Discussionmentioning
confidence: 99%
“…Whether a long or short waiting period after radiotherapy is necessary still is a matter of debate (11,12). In the cohort diagnosed and treated in the Zaans Medisch Centrum, a longer waiting period results in a better outcome (13).…”
Section: Discussionmentioning
confidence: 99%
“…As patients with rectal cancer receive neoadjuvant treatment in the period between diagnosis and surgery, there is ample time for physical training. This relatively long time frame can support the optimization of functional capacity in individual patients, thus allowing for improved recovery …”
Section: Introductionmentioning
confidence: 99%
“…Our study showed no statistical differences for theresults of total spine flexion, inhalation–exhalation difference and rectus abdominis muscle strength in terms of neoadjuvant or adjuvant treatment. Other studies haveshownthe influence of peri- and postopertive treatment onfunctional capacity [ 33 , 34 ], but spinal mobililty, inhalation–exhalation difference and rectus abdominis muscle strength had not been measured yet.…”
Section: Discussionmentioning
confidence: 99%